Identifikasi Potensi Sebaran Mangan Bawah Permukaan di Daerah Oenesu Kecamatan Kupang Barat Kabupaten Kupang - Maria M.T. Olla; Hadi Imam Sutaji; Jonshon Tarigan; Bernandus; Ali Warsito (Jurnal Pendidikan dan Ilmu Fisika, 2026)
Research utilizing the geomagnetic method was conducted to identify the potential distribution of subsurface manganese in the Oenesu area, West Kupang District, Kupang Regency. Data comprising total magnetic field and diurnal variation measurements were acquired using a G-856AX Proton Precession Magnetometer via the looping method across 119 measurement points spaced at 35 meter intervals. The data underwent diurnal and IGRF corrections, upward continuation, 2D modeling and interpretation. The interpretation of magnetic anomalies revealed high anomaly values ​​40 nT to 240 nT, moderate anomalies -60 nT to 40 nT, and low anomalies -160 nT to -60 nT. Modeling results indicate a subsurface lithology composed of limestone susceptibility 0.001200 SI to 0.080327 SI, claystone susceptibility 0.000380 SI to 0.008349 SI, and sandstone susceptibility 0.000001 SI to 0.000999 SI. Correlating these indications with the magnetic anomalies and the typical geological associations of manganese suggests that the manganese deposits are likely associated with the limestone and claystone units. Integrating the modeling results from three cross-sections with the magnetic anomaly values ​​indicates that the potential manganese distribution is predominantly located in the southern, southeastern, and northern parts of the study area, at depths ranging from 9.55 m to 107.28 m.